KEANEKARAGAMAN DAN POTENSI FLORA DI GUNUNG HALIMUN DAN SEKITARNYA DI TAMAN NASIONAL GUNUNG HALIMUN - Tahan Uji (Research Center for Biology-Indonesian Institute of Sciences, 2002)
Gunung Halimun National Park is one of the largest remnants of the tropical rain forest left in Java. The forest in this area is an interesting site to be studied due to the richness,diversity and potential of its flora. Through the intensive explorations in Mt. Halimun, Mt. Ci Timur and Mt.Panenjoan, 275 species of plant have been collected.Six species of them are determined as a rare and vulnerable plants, namely Alyxia rcinwardlii, Elaeocarpus grandiflorus, Symplocos odoratissima, Calamus adspersus, C. ciliaris and Korthalsia junghuhnii;and 10 species as